Josep, help! strengthening multiplication and division through a visual activity book - Toliongco, Karmela Yvonne I.
Obvious efforts to enhance Mathematics education in the Philippines is seen through the development of curriculum guides by DepEd and SEI-DOST. But to this day many Filipino students still struggle on their Math subject. There are numerous possible elements that can contribute to Mathematics difficulty such as the teacher, methods of teaching, teaching materials, the students' own belief and attitudes towards mathematics and in their capabilities which affects them as math learners.